Polyetheretherketone with citrate potentiated influx of copper boosts osteogenesis, angiogenesis, and bacteria-triggered antibacterial abilities. (30th April 2021) - Yan, Jianglong; Xia, Dandan; Xiong, Pan; Li, Yangyang; Zhou, Wenhao; Li, Qiyao; Wang, Pei; Zheng, Yufeng; Cheng, Yan
Graphical abstract: Highlights: It was found that citrate can facilitate 2-fold influx of copper into cells. Polydopamine controlled the switch of implant's bio-function through manipulating the release amount of copper and citrate. The synergistic antibacterial ability between copper and citrate killed 93 % bacteria. Copper and citrate can regulate different pathways of bone formation, thus enhanced osteodifferentiation of Ad-MSC in vitro and promoted new bone formation and osseointegration in vivo . Abstract: A well designed coating for polyetheretherketone (PEEK) implants can provide enough support to overcome crucial medical challenges, which are insufficient osseointegration and high rate of infection. Herein, we utilize the co-deposition of polydopamine (PDA) and copper-citrate nanoclusters to construct a pH-responsive coating on porous PEEK for synergistic bone regeneration, vascular formation and anti-infection. Specifically, this PDA coating released high dose of copper and citrate at lower pH value, which increased intracellular copper content, boosted production of reactive oxygen species and severe damage of protein, leading to killing of 93 % planktonic bacterial and eradication of adherent bacteria. At pH of 7.4, the release of copper and citrate were in a slow and sustained behavior, synergistically enhanced vascular formation potential and osteodiffereration of Ad-MSC in vitro . After implanted in rabbit tibia for 6 and 12 weeks, the micro-CT evaluation and histological analysis consistently highlighted the ability of this PDA coating to increase new bone formation adjacent to coated PEEK implant and enhance bone-implant interfacial integration. These results were proven to be related to the synergistic effect that citrate facilitated a 2-fold influx of copper into cells, which not only enhanced the bacteria-killing ability but also encouraged bone regeneration of implants. This present work provides an effective method to control infections while promoting osseointegration simultaneously, which will show tremendous clinical application and can be a solution to current challenges facing orthopedics.